Advances in the display quality of dye-doped polymer-dispersed liquid crystal films by addition of disc-shaped multidirectional light-control film. Issue 20 (13th November 2017) - Ahmad, Farzana; Jamil, Muhammad; Lee, Jin Woo; Lee, Kyeong Nang; Jeon, Young Jae
Abstract: Typically, the addition of a dye is considered to increase the contrast ratio (CR) of a polymer-dispersed liquid crystal (PDLC) display; however, with the addition of a small amount of dye, the contrast ratio (CR) unexpectedly decreased as compare to the CR of a normal white PDLC display, attributed to various reasons. In this study, an additional multidirectional light scattering polymer film is developed over a conventional dye-doped polymer-dispersed liquid crystal (DPDLC) film to enhance the CR. For this, a disc-shape (DS) pattern on PN393 film is coated. This structure is believed to enhance the scattering properties of DPDLC displays via multiple-directional scattering nature of DS pattern film. Fabrications of such devices are simple and have advantageous of its low-cost production. This optimal designed disc-shaped light-scattering (DSS) film resulted in the enhancement of the CR of the DPDLCs.